Evaluasi karyawan UMKM Kecil Dalam Menstabilkan Pelayanan Di Risoles Gr.Yummy13 - Sri Gina Annisa; Zakky Zamrudi; Syahrial Shaddiq (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2025)
Culinary micro, small, and medium enterprises (MSMEs) play a crucial role in supporting local economies, particularly by creating job opportunities and maintaining service stability for consumers. However, fluctuations in employee performance often affect the consistency of service quality. This study aims to analyze the role of employee performance evaluation in maintaining service stability within culinary MSMEs. The research employed a descriptive qualitative method, using observations, interviews, and questionnaires distributed to business owners and employees of culinary MSMEs in the study area. Data were analyzed thematically to identify patterns linking performance evaluation systems with service quality. The results indicate that regular, feedback-based, and development-oriented performance evaluations can enhance employee motivation, responsibility, and service consistency. Conversely, evaluations that are unilateral or lack transparency tend to decrease work enthusiasm and lead to unstable service performance. Therefore, implementing participatory performance evaluations is essential to achieve stable and sustainable service delivery in culinary MSMEs.